Decreased HHV-6 IgG in Alzheimer’s Disease - Westman, Gabriel; Blomberg, Jonas; Yun, Zhibing; Lannfelt, Lars; Ingelsson, Martin; Eriksson, Britt-Marie (Frontiers in Neurology, 2017)
Human herpesviruses have previously been implicated in the pathogenesis of Alzheimer’s disease (AD) but whether they are causal, facilitating, or confounding factors is yet to be established. A total of 50 AD subjects and 52 non-demented (ND) controls were analyzed in a multiplex assay for IgG reactivity toward herpes simplex virus (HSV), varicella zoster virus (VZV), cytomegalovirus (CMV), and human herpesvirus 6 (HHV-6). The HHV-6 IgG reactivity was significantly lower in AD subjects compared to ND controls, whereas there were no differences in HSV, VZV, or CMV antibody levels between the groups. Analysis of peripheral blood mononuclear cells with a subtype-specific HHV-6 PCR revealed no signs of reactivation, as AD and ND subjects presented with comparable HHV-6 DNA levels in PBMCs, and all positive samples were of subtype B. Whether HHV-6 is a factor in AD remains to be elucidated in future studies.